2020
DOI: 10.1016/j.cmet.2020.04.021
|View full text |Cite
|
Sign up to set email alerts
|

Association of Blood Glucose Control and Outcomes in Patients with COVID-19 and Pre-existing Type 2 Diabetes

Abstract: Although type 2 diabetes (T2D) is a major comorbidity of novel coronavirus disease 2019 (COVID-19), the impact of blood glucose control on the degree of medical interventions required and on all-cause mortality of patients with COVID-19 and pre-existing T2D remains unclear. Here, Zhu et al. report that among $7,300 individuals with COVID-19 (among which nearly 1,000 had T2D) in Hubei Province, China, those with T2D had significantly increased medical interventions and mortality risk. But among the patients wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

87
1,460
15
56

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 1,417 publications
(1,694 citation statements)
references
References 35 publications
87
1,460
15
56
Order By: Relevance
“…In this study which had relatively rich clinical data, we found that diabetes alone was not the independent risk factors for in-hospital mortality of COVID-19, but comorbidities such as hypertension, CKD were risk factors, this result was consistent with the previous study [13]. Partially consistent with the previous studies, our study found that, compared with non-diabetic patients, diabetic COVID-19 patients were older, had worse outcome including higher rate of mortality, severe cases and ARDS, presented severe in ammation response, lung and coagulation dysfunction [2,11,12,14]. Additionally, diabetic patients had increased level of urea nitrogen and decreased level of albumin.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…In this study which had relatively rich clinical data, we found that diabetes alone was not the independent risk factors for in-hospital mortality of COVID-19, but comorbidities such as hypertension, CKD were risk factors, this result was consistent with the previous study [13]. Partially consistent with the previous studies, our study found that, compared with non-diabetic patients, diabetic COVID-19 patients were older, had worse outcome including higher rate of mortality, severe cases and ARDS, presented severe in ammation response, lung and coagulation dysfunction [2,11,12,14]. Additionally, diabetic patients had increased level of urea nitrogen and decreased level of albumin.…”
Section: Discussionsupporting
confidence: 92%
“…Lots of studies had demonstrated that diabetic patients had higher risk of mortality in COVID, as well as developing more severe cases [2,4,11,12]. Guo et al [12] reported that diabetes was a risk factor for the progression and prognosis of COVID-19.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Afterward, based on the cause of their wound, we classi ed patients with chronic wounds as gangrene due to vascular occlusion, ulcers due to traumatic infection, and other types of soft tissue infection wound due to bedsores, gout ruptures, stabbing. Risk factors for coronavirus were limited to advanced age (≥ 60 years), hypertension, diabetes, renal damage, and cardiovascular disease according to the available studies (3,11,27).…”
Section: Methodsmentioning
confidence: 99%